Methods to accelerate fracture healing – a narrative review from a clinical perspective - Ganse, Bergita (Frontiers in Immunology, 2024)
Bone regeneration is a complex pathophysiological process determined by molecular, cellular, and biomechanical factors, including immune cells and growth factors. Fracture healing usually takes several weeks to months, during which patients are frequently immobilized and unable to work. As immobilization is associated with negative health and socioeconomic effects, it would be desirable if fracture healing could be accelerated and the healing time shortened. However, interventions for this purpose are not yet part of current clinical treatment guidelines, and there has never been a comprehensive review specifically on this topic. Therefore, this narrative review provides an overview of the available clinical evidence on methods that accelerate fracture healing, with a focus on clinical applicability in healthy patients without bone disease. The most promising methods identified are the application of axial micromovement, electromagnetic stimulation with electromagnetic fields and direct electric currents, as well as the administration of growth factors and parathyroid hormone. Some interventions have been shown to reduce the healing time by up to 20 to 30%, potentially equivalent to several weeks. As a combination of methods could decrease the healing time even further than one method alone, especially if their mechanisms of action differ, clinical studies in human patients are needed to assess the individual and combined effects on healing progress. Studies are also necessary to determine the ideal settings for the interventions, i.e., optimal frequencies, intensities, and exposure times throughout the separate healing phases. More clinical research is also desirable to create an evidence base for clinical guidelines. To make it easier to conduct these investigations, the development of new methods that allow better quantification of fracture-healing progress and speed in human patients is needed.